Interactive Unawareness and Speculative Trade - Aviad Heifetz; Martin Meier; Burkhard C. Schipper (University of Bonn, Bonn Graduate School of Economics (BGSE), 2003)
The standard state-spaces of asymmetric information preclude non- trivial forms of unawareness (Dekel, Lipman and Rustichini, 1998). We introduce a generalized state-space model that allows for non-trivial unawareness among several individuals, and which satisfies strong properties of knowledge as well as all the desiderata on unawareness proposed this far in the literature. In an example of speculative trade, we demonstrate how mutual unawareness of fundamentals allows for common knowledge of willingness to trade together with strict preference for trade. Such a state of affairs is impossible to model in standard information structures with strong properties of knowledge.
Keywords: C70; D82; D80; C72; 330; unawareness; awareness; knowledge; interactive epistemology; speculative trade; bounded perception; Erkenntnistheorie; Wahrnehmung; Wissen; Information; Theorie